2022
DOI: 10.1523/jneurosci.1800-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Human APOER2 Isoforms Have Differential Cleavage Events and Synaptic Properties

Abstract: Human apolipoprotein E receptor 2 (APOER2) is a type I transmembrane protein with a large extracellular domain (ECD) and a short cytoplasmic tail. APOER2-ECD contains several ligand-binding domains (LBDs) that are organized into exons with aligning phase junctions, which allows for in-frame exon cassette splicing events. We have identified 25 human APOER2 isoforms from cerebral cortex using gene-specific APOER2 primers, where the majority are exon-skipping events within the N-terminal LBD regions compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In this context, Wasser et al, have reported an alternative LRP8 splice variant lacking the O-linked glycosylation region that is cleaved more efficiently than the full-length counterparts [ 130 ]. More recently, it has been shown that LRP8 isoforms with differing numbers of ligand-binding repeats to generate different amounts of CTFs compared with full-length LRP8 [ 135 ].…”
Section: Apolipoprotein E Receptor 2 (Lrp8)mentioning
confidence: 99%
“…In this context, Wasser et al, have reported an alternative LRP8 splice variant lacking the O-linked glycosylation region that is cleaved more efficiently than the full-length counterparts [ 130 ]. More recently, it has been shown that LRP8 isoforms with differing numbers of ligand-binding repeats to generate different amounts of CTFs compared with full-length LRP8 [ 135 ].…”
Section: Apolipoprotein E Receptor 2 (Lrp8)mentioning
confidence: 99%
“…Since APOER2 isoforms have been shown to modify synaptic function and synapse number (Beffert et al, 2005; Omuro et al, 2022), we performed immunofluorescence labeling using antibodies against the presynaptic protein synapsin and the postsynaptic marker PSD95 on Apoer2 knockout mouse neurons rescued with lentiviral human APOER2-FL, control-specific APOER2 Δex4-5, +ex6B, Δex18 or AD-specific APOER2 Δex4-5, +ex6B, Δex15 isoform at 14 DIV where the only difference between these two APOER2 variants is either exclusion of ex15 or ex18. We measured the number of synapsin and PSD95 puncta independently and the number of synapses defined by the colocalization of synapsin and PSD95 (Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between ligands and receptors such as APOER2 do not appear to be explained by simple binding patterns to single ligand-binding repeats, as exon-skipping removes individual domains but also changes overall structure and folding of the receptors. We observed that some exon skipping events in APOER2 lead to increased CTF formation, while others lead to decreased CTF formation, suggesting that receptor folding is a key factor in determining function (Omuro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations